ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG DI PASAR KECAMATAN PANGKATAN - Khairun Nisa; M. Sahnan (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2021)
Many factors influence the income of sellers. This research was aimed to examine the possible factors that affected the amount of income obtained by sellers of Pangkatan Market on Labuhanbatu Regency. This research was categorized as a descriptive research using quantitative method. This research was conducted in Pangkatan Market with 146 population of sellers. The samples in this research were 95 respondents taken by using Proportionate Stratified Random Sampling technique. Meanwhile the method of data  collection  were  using  questionnaires  and  conducting  interview.  The variables used included business capital (X1), education level (X2), the duration of business practice(X3), working hours (X4) and sellers’ income (Y). The data analysis used was Multiple Linear Regression (OLS) with level of significance of 5%. The result of the research showed that partially the variables of business capital (X1) and working hours (X4) had significant effect to the income of sellers in  Pangkatan  Market.  Meanwhile  the  variables  of  education  level  (X2)  and  the duration  of  business  practice  (X3) partially  did  not  give  significant  effect  to sellers’  income  in  Pangkatan  Market on Labuhanbatu Regency.  Next,  the  variables  of  business  capital, education level, and working hours similarly gave significant influence towards the sellers’ income in Pangkatan Market. The influence was in the percentage of 52,6% and the remaining 47,4% is affected by the other variables.